1995
DOI: 10.1111/j.1600-0420.1995.tb00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for ocular dysfunction in children: Approaching a common program

Abstract: . According to the general principles of screening, detection of visual impairment in children is worthwhile, since the condition is a serious health problem, reliable diagnostic tests are available and effective treatment is possible in most instances of ocular and visual dysfunction. However, an evaluation of the screening procedures has not been properly done and the cost‐benefit of screening has not been studied. The aim of the present study is to perform a systematic analysis of the screening programs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 58 publications
1
18
0
4
Order By: Relevance
“…1998). A systematic analysis of screening programmes in Sweden and Canada recommended that screening of visual acuity should be performed at around 4 years of age, and then repeated throughout the school years (Lennerstrand et al . 1995).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1998). A systematic analysis of screening programmes in Sweden and Canada recommended that screening of visual acuity should be performed at around 4 years of age, and then repeated throughout the school years (Lennerstrand et al . 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The detection of amblyopia (and or predisposing conditions) is the component of vision screening in children most supported by evidence (Snowdon & Stewart-Brown 1997), although overall there was limited high-quality evidence supporting vision screening programmes identified in this review. The better quality systematic reviews and RCTs found that screening in the younger years (from 18 months to school age) yielded high detection rates, particularly for amblyopia, and the best opportunities for future improvements of visual pathology (Lennerstrand et al 1995;Weinstock et al 1998;Williams et al 2001Williams et al , 2002. This is supported by non-RCTs indicating that screening between the ages of 3 and 5 years is effective and yields reliable results (Fathy & Elton 1993;Atkinson et al 1996Atkinson et al , 2007Kvarnstrom et al 1998Kvarnstrom et al , 2001Eibschitz-Tsimhoni et al 2000).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…All screening tools described here are designed to be used by nonophthalmological personnel, with minimal training including physicians, school health nurses, etc (13).…”
Section: Vision Testing Methodsmentioning
confidence: 99%